MOTIVASI BELAJAR, PENGGUNAAN INTERNET DAN KREATIVITAS DALAM MENGERJAKAN TUGAS SEKOLAH PADA SISWA SMA 24 JAKARTA - Selviana; Novembi Septiyanti (Fakultas Psikologi Universitas Borobudur, 2024)
This study aims to determine the relationship between learning motivation and internet use with the creativity of grade XI students at SMA 24 Jakarta in doing schoolwork. In this study, the dependent variable is creativity and the independent variable is learning motivation and internet use. The sampling technique used was saturated sampling totaling 161 students with quantitative research. This research instrument uses three Likert scale models consisting of creativity scale, learning motivation scale, and internet use scale. The data analysis technique used is multivariate correlation. The results of this study show that 1) there is a positive relationship between learning motivation and creativity, 2) there is a positive relationship between internet use and creativity, and 3) there is a positive relationship between learning motivation and internet use with creativity. Keywords: creativity, learning motivation, internet use.